2010
DOI: 10.3109/09638280903419277
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and perceptions towards disability and sexuality

Abstract: Stigma can lead individuals to internalise concepts of asexuality and may negatively impact confidence, desire and ability to find a partner while distorting one's overall sexual self-concept. Societal attitudes and perceptions are driven by education and knowledge, if there is no exposure to sexuality and disability, it follows suit that society would have a narrow understanding of these issues. Further research should focus on how best to educate and inform all members of society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
177
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(183 citation statements)
references
References 26 publications
2
177
1
3
Order By: Relevance
“…The absence of gender focus may be attributed to the assumption of asexuality or infantilism linked to disability, 21,58,71,72 the gender neutrality of health care, 6,72,73 unexamined assumptions of the nondisabled community, 74,75 the predominance of gender similarities over differences, 76,77 the salience of disability over gender 78 or the tendency to see disability as the dominant identity marker. 21,[79][80][81] SCI has multiple ramifications for personal, social, professional and domestic responsibilities and, while gender is not the only, and not even necessarily the most important, social identity, it is 'the most pervasive, visible and codified' .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of gender focus may be attributed to the assumption of asexuality or infantilism linked to disability, 21,58,71,72 the gender neutrality of health care, 6,72,73 unexamined assumptions of the nondisabled community, 74,75 the predominance of gender similarities over differences, 76,77 the salience of disability over gender 78 or the tendency to see disability as the dominant identity marker. 21,[79][80][81] SCI has multiple ramifications for personal, social, professional and domestic responsibilities and, while gender is not the only, and not even necessarily the most important, social identity, it is 'the most pervasive, visible and codified' .…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of how these impairments may impede sexual expression is paramount, as is a skill base that allows the treating clinician to provide interventions to overcome and/or compensate for them as relevant to the LGBTQIA+ population (Zasler & Martelli, 2011). Healthcare providers often times incorrectly make the assumption that people with disabilities are not "sexual" or sexually active, which is often far from true (Esmail, Darry, Walter, & Knupp, 2010). On the contrary, a study revealed that women with physical disabilities have as much sexual desire as non-disabled women (Nosek, Howland, Rintala, Young, & Chanpong, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, health care providers often lack education concerning sexological issues, and their attitudes towards working to promote sexual health can be challenged by their own believed non-importance of sexual health for persons with disease or disability (Esmail, Darry, Walter, & Knupp, 2010;Low & Zubir, 2000). Sexual health is strongly related to feelings of well-being and general health (Field et al, 2013;Lindau & Gavrilova, 2010;Ratner, Erekson, Minkin, & Foran-Tuller, 2011), and previous research has shown that rehabilitation can promote sexual health (Kristina Areskoug- Josefsson & Gard, 2015;K.…”
mentioning
confidence: 99%